A Pathway Approach to the Study of Bias Crime Offenders, United States, 1990-2018 - Jensen, Michael ([Verlag nicht ermittelbar], 2024)
This project sought to improve understanding of the characteristics of bias crime in the United States by collecting and analyzing data on a national sample of offenders. The database - The Bias Incidents and Actors Study (BIAS) - includes information on 966 adult offenders who committed hate crimes in the United States from 1990-2018. BIAS includes offenders who committed crimes that were motivated by bias based on (1) race, ethnicity, or ancestry; (2) religion; (3) sexual orientation, gender, or gender identity; (4) disability; and (5) age. BIAS includes more than 100 variable fields that cover all aspects of an offender's background, including their demographic characteristics, family dynamics, education and employment histories, mental health concerns, criminal records, peer associations, and hate group affiliations. BIAS also include details on the nature of the offender's crime, such as whether it was violent or non-violent, spontaneous or premeditated, or was perpetrated alone, with a group, or while under the influence of drugs and alcohol.